A roadmap for genome projects to foster psychosocial and economic evidence to further policy and practice - Claudia Ching Yan Chung; Annie Tsz Wai Chu; Brian Hon Yin Chung (Communications Medicine)
Abstract Advances in genomic sequencing (GS) have transformed personalised treatment strategies for genetic diseases across a diverse array of clinical indications, resulting in notable public health progress. However, limited evidence on the broader psychosocial and economic impacts hinders its widespread adoption in healthcare systems. The launch of genome projects offers an opportunity to address the unmet needs of a wide range of genetic diseases. This Perspective examines the multi-dimensional effectiveness of GS and summarises indicators and measurement tools for psychosocial and economic outcomes. It highlights priority areas identified by the Clinical Sequencing Exploratory Research Consortium. Drawing on initiatives such as the Genomics England 100,000 Genomes Project and Australian Genomics initiative, this article showcases best practices in selecting outcome measures for assessing the effectiveness of GS in policy and practice. This Perspective intends to equip future studies with a strategic and sustainable approach for outcome-oriented research within genome projects, facilitating evidence-based clinical implementation of GS in an appropriate, equitable and efficient manner.